2016
DOI: 10.1111/cen.13166
|View full text |Cite
|
Sign up to set email alerts
|

Association of FOXE1 polyalanine repeat region with thyroid cancer is dependent on tumour size

Abstract: FOXE1 polyalanine repeat polymorphisms are associated with thyroid cancer, but only for tumours larger than 1 cm, suggesting a role in disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Clinical parameters (age at diagnosis, gender, tumor subtype, tumor size, presence of lymph node, or distant metastasis) were analyzed to assess if genetic susceptibility was limited to subgroups of patients, which has been reported for other genetic variants [12,25,26]. Our study revealed a decreased frequency of the CYP2R1 rs2060793 (G > A) minor allele in patients with metastatic disease (OR 0.61, 95% CI 0.40–0.93), which suggests a protective effect of this SNP against more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical parameters (age at diagnosis, gender, tumor subtype, tumor size, presence of lymph node, or distant metastasis) were analyzed to assess if genetic susceptibility was limited to subgroups of patients, which has been reported for other genetic variants [12,25,26]. Our study revealed a decreased frequency of the CYP2R1 rs2060793 (G > A) minor allele in patients with metastatic disease (OR 0.61, 95% CI 0.40–0.93), which suggests a protective effect of this SNP against more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…The control group consisted of 500 (113 males and 387 females, mean age ± SD = 35.9 ± 14.2 years) Caucasian Portuguese unrelated volunteers who were recruited among blood donors from the same geographical area. Cases and controls were the same as those used in a previous study showing an association of FOXE1 variants with thyroid cancer [12], with some replacements due to missing DNA samples. The study was approved by the local research ethics committees (Portuguese Institute of Oncology of Coimbra, and Faculty of Health Sciences, University of Beira Interior, Ref: CE-FCS-2012-011).…”
Section: Methodsmentioning
confidence: 99%
“…FOXE1 (Forkhead Box E1), a Forkhead (FOX) transcription factor is essential for thyroid gland development [ 3 9 ], and is also required in the hormonal regulation of thyroglobulin ( TG ) and thyroid peroxidase ( TPO ) gene expression by the adult thyrocyte [ 10 12 ]. Recent genetic studies have identified germline allelic variation in and near FOXE1 to be strongly associated with non-medullary thyroid cancer risk including single nucleotide variants rs965513[A] (56 kb upstream of FOXE1 ) [ 13 18 ] and rs1867277[A] (within its promoter) [ 19 21 ], and variation within the FOXE1 polyalanine tract [ 22 24 ]; resolution of causal variants responsible for the association with thyroid cancer has been difficult due to strong linkage disequilibrium between all three variants. Nevertheless, these allelic variants were associated with altered FOXE1 expression in PTC tissues [ 25 ], whereas complete loss of FOXE1 expression is often found in anaplastic thyroid cancer (ATC) [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%